Estimation and Correction for the Temperature Lag in Thermoluminescent Measurements for LiF: Mg, Cu, Na, Si Phosphor - Ha, Vu Thi Thai; Hai, Nguyen Thi Quy; Long, Nguyen Ngoc (Communications in Physics, 2011)
In the current work the glow curves for LiF:Mg,Cu,Na,Si thermoluminescent material were measured at various heating rates in the range from 1 K/s to 30 K/s. In the thermoluminescent measurements a contact heating was used to heat the powder samples. The temperature lag between the heating element and the dosimeter was estimated and corrected by applying Kitis-Tuyn's method. Some kinetic parameters of the traps in LiF:Mg,Cu,Na,Si were evaluated using a variable-heating-rate method.